Investigation and quantification of bioactive compounds from leaf extract of Acacia arabica as an effective antibacterial agent against E.coli associated with diarrheal infections - Biswas, Deboshree; Shanti, V; Roymon, M G (Journal of Phytology, 2012)
In this study antibacterial effect of bioactive compounds present in crude methanolic leaf extract of Acacia arabica was investigated against four different E.coli serogroups associated with diarrheal infections in animals. The serogroups were E.coli O22, O11, O89 and O61 along with one standard E.coli strain carrying LT and ST enterotoxins. Separation and identification of bioactive compounds was carried out by CC (Column chromatography), Preparative HPLC coupled with LC TOF ESI MS. Determination of antibacterial activity was carried out by well diffusion and broth microdilution method. The main compounds were identified including, methyl 3,4,5 tri hydroxyl benzoate (C8H8O5), p-coumaroyl glucoside (C15H19O7), p -coumaroyl quinic acid (C16H18O8), Ferulic acid (C10H10O4), isoferulic acid, epi catecine-3-gallate (C22H18O10), ascorbic acid , quercetine 3-O- (4’-O-acetyl)-rhamnopyranoside (C28H30O16), oleic acid (C18 H34O2), myristic acid (C14H28O2), Palmitic acid (C16H32O2) and steroidal sapogenin aglycons. The compound p-coumaroyl glucoside and p -coumaroyl quinic acid was obtained in combined form and largest antibacterial efficacy was observed in this combination. In addition, Ferulic acid and sapogenin aglycon was found to be having antibacterial potential.